Show me the data: A statewide comparative report of National Healthcare Safety Network (NHSN) Antimicrobial Use Option standardized antimicrobial administration ratios (SAARs) - Hana R. Winders; Kayla Antosz; Majdi Al-Hasan; P. Brandon Bookstaver; Pamela Bailey; Katie Waites; Julie Ann Justo (Cambridge University Press, 2022)
The Antimicrobial Stewardship Collaborative of South Carolina created quarterly Comparative SAAR Analysis Reports based on standardized antimicrobial administration ratio (SAAR) data from the NHSN Antimicrobial Use (AU) Option. These reports provide SAAR histograms and site-specific feedback to participating facilities in South Carolina. They were created to improve antimicrobial use throughout the state, especially in rural regions.